Relationship between match running performance and physical capacity in Malaysia young soccer players - Atan, S. A.; Azli, M. S.; Jakiwa, J.; Rustam, S. (SportMont, 2023)
Monitoring players during match play has become a fundamental approach to gain understanding on soccer demands. Considering there has been growing interest in performances of young players, it is important to understand on young players training requirement. Therefore, the aim of this study was to examine the relationship between match running performance and physical capacities in U15 young soccer players. Twenty outfield players from sports school and academy (n=20, 1.63±0.8 m, and 56.1±9.5 kg) volunteered to participate in the study. Match running performance was analysed during two matches for each player using 5 Hz global positioning system. The participants performed the Yo-Yo Intermittent Recovery Level 1 (YYIR1), Countermovement Jump (CMJ) and 20 m Sprint to determine the physical capacities. The results showed there were no significant relationship between; total distance covered and YY1R1, sprint distance and leg power, maximum sprint speed during matches (km.h -1) with 20 m sprint (P>0.05). These results suggest that physical capacity test should not be used as a single factor in recognizing a young player`s potential to excel and to predict soccer performance. Young players may not need extraordinary capacity; however, they must possess a reasonably high level within all areas to be a good player.